Antiaging Activity of Antioxidant Compounds Produced by Streptomyces sp. SAE4034 on Saccharomyces cerevisiae - Ryandini, D.; Maulida, D.A.; Ameylia, B.; Aziz, S.; Satwika, T.D. (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Streptomyces sp. SAE4034 is known to produce antioxidant compounds; however, its potential as an antiaging agent has yet to be established. The antiaging effect in vivo can be evaluated through cellular analysis by mitochondrial staining in Saccharomyces cerevisiae cells and by measuring the expression of the sty1 and pap1 genes in yeast cells subjected to oxidative stress. This study investigated the impact of antioxidant extract administration at concentrations of 250, 500, 750, and 1000 μg/mL on the viability of yeast cells exposed to oxidative stress induced by H₂O₂. Treatments were assessed on the 7th and 11th days of incubation, with three replicates per treatment. Cellular-level observations focused on treatments demonstrating the most pronounced antiaging activity, alongside controls. Molecular-level analyses involved evaluating the expression of the pap1 and sty1 genes. The primary parameter measured was yeast colony diameter, supported by mitochondrial staining intensity and gene expression data. Results indicated that the crude extract of Streptomyces sp. SAE4034 exhibits antiaging properties in S. cerevisiae cells. Specifically, the extract at 250 μg/mL effectively maintained yeast cell viability under oxidative stress induced by 3 mM H2O2 on both the 7th and 11th days of incubation. Mitochondrial activity assessments revealed strong fluorescence intensity following treatment with 250 μg/mL of the crude extract. Electrophoresis analysis demonstrated a sixfold reduction in pap1 gene expression in the 250 μg/mL treatment group compared to the negative control. Expression of the sty1 gene, however, was not detected.